Data security problems in the urban organizational structure - Marlena Wilk; dr Marta Daroń (Nowoczesne Systemy Zarządzania, 2018)
The article deals with issues related to technological development and its impact on the functioning of urban entities. There were described some IT problems, that enterprises and institutions of the public sector have to face nowadays. The main trends in the digitization process, which influence strong the local public sector, were identified. The attention was paid to the issue of collecting and processing the data by urban organizational entities, and the security of these data.